Telejornalismo, interação e redes sociais: convergências na TV Cabo Branco e TV Paraíba - Pereira, Ana Maria de Sousa (2014)
Grab the remote and passively watch the television programming is a habit of the past. We are living in the technological era, marked by the speed on the search and transmission of information that generate changes in the way we produce and share the news. More than just an entertaining space, the internet has become a daily source of knowledge. For decades, television has influenced the culture, in speeches and in consumer desires and technological advances have forced this to reinvent itself. In this context, the spread of social networks, Facebook and Twitter profiles, combined with scan data and possibilities of interaction generates a revolution in communications, specifically in television journalism. Given this scenario, the main objective of this dissertation is to analyze the implications of social networks in the production of TV journalism "Cabo Branco TV" and "Paraíba TV", both affiliated stations from Rede Globo, in Paraíba state, considering the viewers, in addition to being consumers news also assume the role of agents in building collaborative information. For the study we deal with concepts of convergence, interaction and participatory culture. This is an empirical analysis of a qualitative nature, whose purpose is exploratory and explanatory methodology, in which we performed literature search, data collection, posted on Facebook and Twitter broadcasters, visit productive routine and conducting interviews. These resources allow us to map the interactions between broadcasters and their viewers to identify results in the fields of verification, production and distribution of content in journalism. Through our analysis, we conclude that social networks beyond the idea of entertainment and are becoming important areas of collaboration for television journalism. The facility and speed with which information circulates through this environment opens a field of possibility for changes in the formats of newspapers TV.